2017
DOI: 10.1039/c6dt04490e
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of two magnetic interaction states in dinuclear Dy(iii) complexes via subtle structural variations

Abstract: Herein we explored the transitions of two magnetic interaction states (antiferromagnetic or ferromagnetic) upon structural variations in two dinuclear Dy(iii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…There are still little investigated on another important factors of molecular magnetism, namely, magnetic exchange interactions and magneto-structural correlations. [13][14][15][16][17][18] There are mainly the following reasons for the lack of research in this area: the rst reason is the deep-seated nature of the 4f orbitals and the associated very weak exchange interactions. The second reason is that it is difficult to understand even the nature of exchange interactions, because the prole of the product of susceptibility and temperature versus temperature is dominated by the variation in the population of the Stark levels.…”
Section: Introductionmentioning
confidence: 99%
“…There are still little investigated on another important factors of molecular magnetism, namely, magnetic exchange interactions and magneto-structural correlations. [13][14][15][16][17][18] There are mainly the following reasons for the lack of research in this area: the rst reason is the deep-seated nature of the 4f orbitals and the associated very weak exchange interactions. The second reason is that it is difficult to understand even the nature of exchange interactions, because the prole of the product of susceptibility and temperature versus temperature is dominated by the variation in the population of the Stark levels.…”
Section: Introductionmentioning
confidence: 99%
“…As P QTM 2 is smaller than P QTM , QTM is effectively suppressed in coupled dimers of SMMs . In the case of 4f SMMs, with a few exceptions, through‐space magnetic dipole–dipole (MD) interactions have a significant effect on the SMM behavior . When the magnetic easy axes of the magnetic dipoles are on the same straight line, only an axial component of the MD interactions exists, which scarcely affects P QTM , making P QTM 2 small.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In the case of 4f SMMs, with af ew exceptions, [10][11][12][13] through-space magnetic dipole-dipole (MD) interactions have as ignificant effect on the SMM behavior. [14][15][16][17][18][19][20][21][22][23][24][25] When the magnetic easy axes of the magnetic dipoles are on the same straight line, only an axial component of the MD interactions exists, which scarcely affects P QTM ,m aking P QTM 2 small. On the other hand, in the presence of transversal MD interactions, P QTM becomes larger,a nd hence, the magnetic relaxations are faster due to the larger off-diagonal matrix elements of the coupled ground states.…”
Section: Introductionmentioning
confidence: 99%
“…While such single ion magnets are certainly of considerable interest there is also substantial interest in dinuclear complexes because of several reasons. One, such complexes serve as the simplest models to understand inter‐lanthanide interactions mediated through ligands . Second, the pioneering work of Long and co‐workers has revealed that having appropriate bridging ligands between the lanthanide centers allows a favorable electronic communication between them .…”
Section: Introductionmentioning
confidence: 99%